2007
DOI: 10.1002/jmri.21204
|View full text |Cite
|
Sign up to set email alerts
|

Voxel‐based analysis of R2* maps in the healthy human brain

Abstract: Purpose: To develop a voxel-based analysis of an R2* map of healthy human brain that is automatic, reproducible, and realizable in a single examination on a 3T MR imager. Such a tool could be useful to measure iron accumulation in neurodegenerative diseases. Materials and Methods:In all, 18 healthy subjects underwent MR imaging at a field strength of 3T: 1) six consecutive T2*-weighted gradient-echo volumes were acquired using a segmented echo-planar imaging sequence and 2) a conventional dual-echo turbo spin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
74
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 40 publications
15
74
0
Order By: Relevance
“…Elevated iron concentrations have been observed in normal aging (Stankiewicz et al, 2007) and may contribute to myelin susceptibility (Bartzokis, 2004). Protracted maturational T2 alterations may persist into the third decade of life (Hassink et al, 1992) and quantitative relaxation studies have shown age-related alterations in T2 and T2* relaxation (Bartzokis et al, 1997;Bartzokis et al, 2004;Péran et al, 2007;Siemonsen et al, 2008). Our analyses showed that although cortical GM R2* showed strong age-related variability, including R2* in the statistical models only to a minor extent influenced estimated age effects on intracortical GM MP-RAGE signal intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated iron concentrations have been observed in normal aging (Stankiewicz et al, 2007) and may contribute to myelin susceptibility (Bartzokis, 2004). Protracted maturational T2 alterations may persist into the third decade of life (Hassink et al, 1992) and quantitative relaxation studies have shown age-related alterations in T2 and T2* relaxation (Bartzokis et al, 1997;Bartzokis et al, 2004;Péran et al, 2007;Siemonsen et al, 2008). Our analyses showed that although cortical GM R2* showed strong age-related variability, including R2* in the statistical models only to a minor extent influenced estimated age effects on intracortical GM MP-RAGE signal intensity.…”
Section: Discussionmentioning
confidence: 99%
“…TE range and resolution were chosen similar to those in established protocols at 3T. 9 For R2-mapping, a multi-spin-echo sequence was used with a 1.7-mm in-plane resolution and a 3.4-mm section thickness. Only even echoes were evaluated (at TE ϭ 30, 60, 90, 120, and 150 ms, TR ϭ 4500 ms) because these are not contaminated by stimulated echo signals.…”
Section: Imaging Protocolmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Recent studies advocated SWI as a potential in vivo marker to detect susceptibility changes among tissues, which aids in the identification of paramagnetic nonheme iron (ferritin and transferrin), which would appear hyperintense on filtered phase images. [15][16][17][18] These finding opened a new window to estimate the regional changes in iron content associated with ALS.…”
mentioning
confidence: 99%